Tips for Including Individuals With Autism in Physical Education. Issue 1 (2nd January 2022) - Gordon, Victoria; Pennington, Colin G.
Abstract : As a physical educator, the lowlihood of having a student with Autism Spectrum Disorder (ASD) in your class are extremely high. Autism Spectrum Disorder differs between individuals; it can be high or low functioning. Having these students in the classroom can be challenging at times and you must understand these students and their needs. Not all students with Autism are the same, so they will need individualized accommodations and modifications. Students with Autism are fully capable of participating in physical activities when given the proper supports.